Isolation and Identification of DPPH Radical (2,2-diphenyl-1-pikrylhidrazyl) Scavenging Active Compound in Ethyl acetat fraction of Piper acre Blume - Hifdzur Rashif Rijai; Nanang Fakhrudin; Subagus Wahyuono (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Piper acre Blume, known as Black Betel (local name), is a plant that is widely used by the people of East Kalimantan, especially in Samarinda, for the treatment of illness. Leaves (3-4 months old) are collected from Samarinda, extracted, fractionated, and monitored by DPPH antiradical activity. The isolation of the Piper acre Blume is performed on the active fraction, and the structure identification is based on spectroscopic data of the compound. The leaves were dried, pulverized, and macerated with MeOH. Dried MeOH extract was obtained upon evaporation of the solvent. The extract was then fractionated by vacuum liquid chromatography (vlc), eluted gradually by solvents having different polarities (n-hexane, ethyl acetate and methanol). The fractions obtained were monitored using TLC [n-hexane: ethyl acetate (3: 1 v/v)] that was visualized by UV254 nm, UV366 nm and DPPH. The isolation was performed by preparative TLC [SiO2, n-hexane: ethyl acetate (3: 1)] on ethyl acetate fraction that showed the highest DPPH antiradical value. A single compound was obtained, and it appeared as a round spot and pure according to TLC performances at 3 different solvent systems. The isolated Piper acre Blume compound displayed the IC50 value on the anti-radical DPPH (measured at λ 520 nm) as 10.41µg/mL. The IR spectrum (KBr) showed –OH band (3450 cm-1), aliphatic bands [alkene, 3010 cm-1; alkana 2900 cm-1), an aromatic overtone bands (1900-200 cm-1) and a strong C=O band (1725 cm-1). The NMR (1H- and 13C-) (mono and 2D) indicated the present of a p-di-substituted aromatic signals (δ, 7.54 and 7.52, d, J =6 Hz, 1 H each), 2 methyl (δ, 0.96, d, J = 7.0 Hz, 6 Hs), a triplet signal (δ, 4.22 ppm). Other signals of CH- and CH2 were shown as m signals at δ, 1.64 and 1.34 ppm. Based on those data, the compound was identified as isoamyl p-OH benzoate that is grouped as parabens used as a preservative in the pharmaceutical preparations. In conclusion, the anti-radical (DPPH) active compound present in the leaves of Piper acre Blume is identified as isoamyl p-OH benzoate, having IC50 value anti-radical DPPH 10,41µg/mL.